Diversity and functional characteristics of intestinal microbiome in patients with varicocele - PENG Yisong; LIU Shuang; TANG Li; XIAO Xu; TANG Bo (陆军军医大学学报, 2023)
Objective To investigate the changes of intestinal microbiome in patients with varicocele (VC) with macrogenomics. Methods Fresh feces from 15 VC patients and 15 healthy individuals were collected, and DNA sequences were extracted from the feces. The diversity and functional characteristics were analyzed by metagenome sequencing methods. Results There were no statistical differences in age and body mass index (BMI) between the 2 groups (P > 0.05). The Alpha diversity results showed no significant difference was observed between them (P > 0.05). The Beta diversity results indicated that the species diversity had significant differences in the feces between the VC patients and healthy individuals (P < 0.01). The dominant floras in both the VC patients and healthy individuals were mainly Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria and Fusobacteria. At species level, the dominant floras in VC patients included Flavonifractor plautii, Methanobrevibacter smithii, Enterobacter roggenkampii, etc, and those in the healthy individuals were Phascolarctobacterium faecium, Romboutsia ilealis, Bifidobacterium bifidum, Prevotella jejuni, Clostridium perfringens, etc. Metagenomics data identified significant up-regulation of D-glucarate degradation pathways, including D-galactarate degradation I, superpathway of D-glucarate and D-galactarate degradation, D-glucarate degradation I, etc. The alterations were associated with intestinal microbiomes Enterococcus faecalis, Flavonifractor plautii, Raoultella terrigena, etc. Conclusion There are obvious characteristics changes in microflora structure between VC patients and healthy controls. Up-regulation of D-glucarate degradation pathways are found in VC patients. These changes of intestinal microbiome might be one of the underlying pathophysiological mechanism of VC.